Job satisfaction of the communicator in the practice of public relations: A survey study on private establishments in the United Arab Emirates for the period November 15, 2019 to February 15, 2020 - Abdulaziz, Khalid Ibrahim (Al-Adab Journal, 2020)
This research addressed the job satisfaction of the communicator in the practice of public relations in private establishments in the United Arab Emirates. The research aimed to find out level of job satisfaction of the communicator in public relations in private establishments, through satisfaction for his salary and bonuses, his relationship with their colleagues, his links with their institution’s leadership, clarity of institution's policy, Justice of job development, job stimulation, and work environment. The researcher used media survey methodology and questionnaire as an essential tool for collecting information. Some of the important results of the research are: The level of job satisfaction of the communicator in public relations from his salary and bonuses is very high, the salary he receives is suitable with his duties, this salary encourages him to do work better, the salaries policy followed is fair, the salary he receives meets his needs, and therefore he is completely satisfied with the salary he receives. The research recommends: The institution should review the work method to allow the formation of human relationships between colleagues, the Public relations practitioner is appreciated based on his efforts not on personal and social relationships.